2018
DOI: 10.5546/aap.2018.eng.126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breastfeeding on common pediatric infections: a 5-year prospective cohort study

Abstract: The present study detected that breastfeeding duration longer than 12 months significantly reduces the common childhood infections such as otitis media and gastroenteritis during the first 5 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
0
13
0
1
Order By: Relevance
“…She will also be able to provide information on three areas in which breastfeeding can reduce morbidity: risk of infection, cancer, and obesity. Breastfeeding promotes the development of indigenous flora; thus, protecting infants from infection [43][44][45]. The risk of opportunistic infections contracted in birth points is greater in infants fed on formula than in breastfed infants.…”
Section: Discussionmentioning
confidence: 99%
“…She will also be able to provide information on three areas in which breastfeeding can reduce morbidity: risk of infection, cancer, and obesity. Breastfeeding promotes the development of indigenous flora; thus, protecting infants from infection [43][44][45]. The risk of opportunistic infections contracted in birth points is greater in infants fed on formula than in breastfed infants.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reviews of studies indicated an increased frequency of otitis media in children due to a short breastfeeding period and the introduction of milk formula before six months of age [16]. Extended breastfeeding seems to reduce the incidence of otitis media in childhood [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of breastfeeding on intestinal microbiota development and upper respiratory tract bacterial flora is well known, it is not clearly defined whether topical application of human milk to mucous membranes, e.g., ocular or nasal, brings health benefits. It is generally recognized, however, that microbial dysbiosis in anatomical niches may lead ultimately to immune dysregulation [15,16,17]. From this standpoint, further research on the topic of “breast milk therapy” for mucosal infections is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The preventive effect of breastfeeding on OM has been widely studied. Several studies [13, 52] have shown that even a short duration of breastfeeding might be beneficial for preventing OM. However, in our analysis, the protective effect of breastfeeding against OM was not evident.…”
Section: Discussionmentioning
confidence: 99%